2021
DOI: 10.1002/ueg2.12071
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of duodenal adenomatosis in familial adenomatous polyposis—A case‐based review

Abstract: Adenomatous polyposis (AP) diseases, including familial adenomatous polyposis (FAP), attenuated FAP (AFAP), and MUTYH-associated polyposis (MAP), are the second most common hereditary causes of colorectal cancer. A frequent extracolonic manifestation of AP disease is duodenal polyposis, which may lead to duodenal cancer in up to 18% of AP patients. Endoscopic surveillance is recommended at 0.5-to 5-year intervals depending on the extent of polyp growth and histological progression. Although the Spigelman class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(232 reference statements)
0
5
0
Order By: Relevance
“…For recurrent adenomas, the necessity of rectal resection has not been determined. Some studies have confirmed the success rate of endoscopic resection, but the long-term efficacy of endoscopic therapy remains to be proven due to the high risk of recurrence [ 19 , 20 ]. Proctectomy is radical and advisable for patients without special requirements.…”
Section: Discussionmentioning
confidence: 99%
“…For recurrent adenomas, the necessity of rectal resection has not been determined. Some studies have confirmed the success rate of endoscopic resection, but the long-term efficacy of endoscopic therapy remains to be proven due to the high risk of recurrence [ 19 , 20 ]. Proctectomy is radical and advisable for patients without special requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic surveillance of the GI tract appears to be essential in patients with FAP. Screening colonoscopies in families of FAP patients and prophylactic colectomy in diagnosed patients have importantly reduced the incidence of colorectal cancer [ 21 ]. However, the significantly decreased mortality due to lower GI malignancy substantially raised the importance of upper GI tract endoscopy due to the high risk of duodenal adenomatosis and, as a consequence, duodenal cancer incidence.…”
Section: Duodenal Lesionsmentioning
confidence: 99%
“…This system integrates factors such as the number and size of the adenomas, along with their morphology and the extent of dysplasia 7 . Although the Spigelman classi cation has been validated, it tends to underestimate the importance of ampullary lesions and does not closely correlate with the risk of duodenal cancer [8][9][10][11] . Additionally, it requires obtaining biopsies from duodenal lesions that many endoscopists would prefer to remove completely, either by simple polypectomy or endoscopic mucosal resection (EMR) [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%